Absolute immature platelet counts in the setting of suspected heparin-induced thrombocytopenia may predict anti-PF4-heparin immunoassay testing results. Issue 4 (August 2018) - Chen, Wei; Ha, Jennifer P.; Hong, Hong; Maitta, Robert W.
Abstract: Background: Heparin-induced-thrombocytopenia (HIT) is a disease mediated by antibodies to platelet factor 4 (PF4)-heparin complexes. Immature platelet fraction (%-IPF) and absolute immature platelet count (A-IPC) measure newly-released platelets into circulation and can prove useful in differentiating patients with thrombocytopenic presentations due to consumptive or hypoproduction processes. Therefore, we evaluated utility of A-IPC in a cohort of thrombocytopenic patients suspected of HIT. Patients and Methods: Twenty-six thrombocytopenic patients (<150 × 10 9 /L) tested for anti-PF4-heparin and 36 non-thrombocytopenic controls were included. Platelet count, %-IPF, and A-IPC were determined at time of anti-PF4-heparin testing. Results: Sixteen patients tested anti-PF4-heparin negative and 10 tested positive. Patients with positive anti-PF4-heparin did not differ in A-IPC from normal range (7.2 ± 2.9 × 10 9 /L vs. 7.1 ± 3.2 × 10 9 /L respectively; p  = 0.97). However, there was a significant A-IPC decrease in patients negative for anti-PF4-heparin compared to normal range and those testing anti-PF4-heparin positive (4.2 ± 3.1 × 10 9 /L vs. 7.1 ± 3.2 × 10 9 /L vs. 7.2 ± 2.9 × 10 9 /L respectively, p  < 0.01). An A-IPC of greater than 5 × 10 9 /L characterized 80% of anti-PF4-heparin positive cases. Conclusion: A-IPC measurements can complement anti-PF4-heparin testing of patients suspected of HIT while potentially predicting anti-PF4-heparin immunoassay results.